DIARY DISCOURSE AS A NARRATIVIZATION OF A PERSONAL EXPERIENCE OF O. GONCHAR - Mostova, S. (Linguistic and Conceptual Worldviews, 2019)
The article deals with the linguistic study of discourse which is based on the material of «Dia- ries» by O. Gonchar. In the focus of this research, diary entries are established as the projection and reflection of the linguistic personality of the writer. The process of keeping a diary is considered as the communicative value of text writing. Therefore, the entries reflect the results and characteristics of Gonchar’s communicative activity. The reflection of the word appears as a writer’s artistic work that absorbs the philosophy of his time, his aspiration and cultural experience. Moreover, the linguistic reading of the diary discourse reveals the axiсological perception of the reality, verbalized in the word. As noted by I. Sirko, in the Ukrainian linguistic culture only in the second half of the 20th century – at the beginning of the XXI century dia- ries became a form of personal expression. Due to the philological achievements, it is known that diary and diary activity form the discourse. If to quote the definition of discourse by N. Arutyunova, then discourse is a text immersed in life. Ac- cording to Y. Stepanov, the phenomenon of discourse is the proof of the thesis «Language is the home of the spirit» and, to some extent, the thesis «Language is the home of being». So keeping a diary is a kind of communicative activity. The concept of the diary accurately reflects the specifics of its keeping – a kind of activity that is implemented every day. Linguistic study of the diary’s discourse involves a variety of approaches, including 1) modeling of diary activity, 2) the selection of typical cases of diary writing and the main tendencies characterizing diary texts; 3) description and characterization of diary texts in the unity of language, psycholinguistic, cultural, extra-linguistic circumstances, which influenced the subject and led to creativity. In the diary discourse, we can trace the activities of the author in the role of «figure», the role of «chronicler», the role of «carrier of the psychological state», the role of «the one who writes». This is due to the wide possibilities of the diary. Naturally, in each case, these roles are individual. For example, O. Gonchar realizes himself in several diﬀerent roles, which is reflected in the numerous entries. He includes all the information, such as drafts of letters, scenes of works, heard jokes or stories, interesting facts, personal or other observations, thoughts which the author consid- ered to be deserving for certain reasons to save. O. Gonchar is endowed with a degree of freedom in his communicative activity. He is free not only in the choice of lexical and syntactical means but also in the choice of topics (events) for a diary entry, as well as in measures of detail, describing a particular event. Thus, a diary is the prism of the vision of the writer’s world, the history of his experience and the formation of the author as a person. In addition, it is important to notice that the records often cover the entire life of the author, which allows us to trace the evolution of the linguistic personality, reconstruct the content of its worldview. In this way, diaries provide informational and communicative values, appear as a projection of the linguistic personality of the writer and reflection of the author’s language.